The effect of others' attributions in feedback - Caitlin E. Smith Sockbeson; Angelo S. DeNisi (Organization Management Journal (OMJ), 2023)
Purpose - Research has supported both feedback's variable effects on performance and the effect of attributions on subsequent behavior. Managers' attributions for subordinates' performance affect how they react to those subordinates and the feedback they give, and subordinates' own attributions affect their subsequent behavior. It is unclear whether (or how) a manager's attributions for subordinate behavior affect subordinate behavior. Building on research that shows emotional reactions in response to attributions in feedback, this study aims to examine how recipients' perceptions and subsequent effort and performance are affected when others' attributions are shared through feedback. Design/methodology/approach - Drawing on attribution theory and feedback intervention theory, this study conducts a lab experiment using manipulated performance feedback to test the effects of feedback sign and attributions in the feedback. Perceptions of the attribution are also measured to test their effects. The data were analyzed using analysis of variance and regression in SPSS 27. Findings - Results show that perceptions of the attribution communicated in feedback, rather than feedback sign alone, affect perceived valence of the feedback (e.g. feedback with an attribution to luck is generally perceived as negative). These perceptions also affect feedback acceptance and impact subsequent effort and performance more than the "objective" attribution, underscoring the importance of recipient reactions and perceptions in the feedback process. Originality/value - This paper shows that recipients' perceptions of others' attributions included in feedback impact feedback reactions, effort and performance. This is valuable to scholars researching feedback and to practitioners to better understand how feedback they deliver may be interpreted.
Keywords: 650; Attributions; Feedback; Performance management